Perancangan Sistem CRM Berbasis Web Pada PT. Sinar Komunikasi Nusantara Menggunakan Metode Waterfall - Julyanto Sarwinata, Muhammad; Rizky Fadillah, Muhammad; Afriza, Ivan; Haryono, Wasis (Shofanah Media Berkah, 2025)
PT Sinar Komunikasi Nusantara is an Internet Service Provider (ISP) that faces challenges in managing customer data and handling services due to a fragmented Customer Relationship Management (CRM) system across divisions. This issue leads to slow response times to customer complaints, reduced work efficiency, and limited service personalization. To address these problems, a web-based CRM system was designed and implemented using the Waterfall development methodology. The development stages included requirements analysis, user interface and database design, application implementation, and functional testing. The resulting system provides features such as login, internet package management, complaint submission, and service upgrade/downgrade requests. User testing results indicate that the system is easy to use, enhances operational efficiency, and improves communication between the company and its customers. The implementation of this CRM system enables the company to improve service quality and foster long-term customer relationships.